Behavioral interviewing write a story, tell a story. - Hagevik S (Journal of Environmental Health, 2000)
Dr. Hagevik has agreed to provide NEHA members with a free resume review. If you desire assistance in creating or making revisions to your resume, a reasonable price for this service will be determined based on the extent of work requested. To request a free resume review and/or additional resume services, contact a NEHA Service Specialist at (303) 756-9090 ext. 0.